RAF Suppression Synergizes with MEK Inhibition in KRAS Mutant Cancer Cells - Lamba, Simona; Russo, Mariangela; Sun, Chong; Lazzari, Luca; Cancelliere, Carlotta; Grernrum, Wipawadee; Lieftink, Cor; Bernards, Rene; Di Nicolantonio, Federica; Bardelli, Alberto (Cell reports (Cambridge), 2014)
KRAS is the most frequently mutated oncogene in human cancer, yet no therapies are available to treat KRAS mutant cancers. We used two independent reverse genetic approaches to identify components of the RAS-signaling pathways required for growth of KRAS mutant tumors. Small interfering RNA (siRNA) screening of 37 KRAS mutant colorectal cancer cell lines showed that RAF1 suppression was synthetic lethal with MEK inhibition. An unbiased kinome short hairpin RNA (shRNA)-based screen confirmed this synthetic lethal interaction in colorectal as well as in lung cancer cells bearing KRAS mutations. Compounds targeting RAF kinases can reverse resistance to the MEK inhibitor selumetinib. MEK inhibition induces RAS activation and BRAF-RAF1 dimerization and sustains MEK-ERK signaling, which is responsible for intrinsic resistance to selumetinib. Prolonged dual blockade of RAF and MEK leads to persistent ERK suppression and efficiently induces apoptosis. Our data underlie the relevance of developing combinatorial regimens of drugs targeting the RAF-MEK pathway in KRAS mutant tumors. [Display omitted] •MEK inhibition induces BRAF-RAF1 heterodimerization in KRAS mutant tumor cells•RAF1 and MEK inhibition is synthetic lethal in KRAS mutant colon and lung tumors•Concomitant RAF-MEK inhibition leads to ERK suppression and apoptosis Lamba et al. found that RAF1 suppression is synthetic lethal with MEK inhibition in KRAS mutant colorectal and lung tumors, for which no effective therapies are available. Concomitant inhibition of RAF1 and MEK induces prolonged mitogen-activated protein kinase pathway suppression and apoptosis. These data underlie the relevance of developing combinatorial regimens of drugs targeting both RAF and MEK in KRAS mutant tumors.